Options for achieving a close-to climateneutral EU industry and their implications - Andrea Herbst; Tobias Fleiter; Marius Neuwirth; Matthias Rehfeldt; Jakob Wachsmuth (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2021)
Industry is a critical sector for the achievement of European climate goals, in particular specific energy-intensive products/processes (e.g. steel, cement, ethylene, ammonia). A reduction target of over 90% for industry requires a wide variety of reduction options. While the EU Low-Carbon Roadmap 2011 for the industry sector was still limited to energy efficiency, biomass and CCS, the new long-term climate protection strategy includes further options such as electrification, renewable synthetic energy sources, ambitious recycling management, material efficiency along the value chain and innovative manufacturing processes. For many industries, this transition involves fundamental process changes. Against this background, the paper aims to take a closer look at the implications for the individual sectors. In addition, a more in-depth assessment of material efficiency, substitution and recycling measures in the building sector and the use of hydrogen in the chemical and steel sectors is provided. The paper served as a basis for an input to the event "Decarbonizing industry - Energy and CO2 Saving Potentials in the short and longer term" at the EUSEW 2020 (EUSEW 2020) and is based on previous similar works.
urn:nbn:de:0011-n-6410647
Keywords: 330